Bodhi Tree and Xaunzang with Special Reference to the Buddhist Texts - (Cherdchai Sīlasampanno), Phrakittisarasuthee (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
The aim of this current paper is to study on the Bodhi tree in the recorded of Xuanzang when he pilgrimaged to India and reached the Bodhi tree with reference to the Pali Buddhist texts and commentaries. Xuanzang lived at the beginning of Tang Dynasty, studied in Mahayana Buddhism, Yogacara School being popular in China at that time. When he pilgrimaged to India for study in Nalanda with Silabhadra Thera and had a good knowledge on Sanskrit. He returned to China along with important Buddhist Scriptures in Sanskrit and beginned to translate into Chinese. The great works of him is The Buddhist records of the western world in Tang Dynasty which enabled him to be well-known all over the world. It was the very important historical documents. The Bodhi tree which people from all over the world come to homage is recorded in this work of Xuanzang. Also the story of it contained the concordance with the Buddhist texts.